The challenge of SGI provision in rural areas - Daniel Rauhut; Tomasz Komornicki (European Regional Science Association (ERSA), 2015)
The access to Services of General Interest (SGI) is a highly relevant factor for territorial cohesion and in creating economic opportunity. Although the topic of SGI was not on the top of the policy agenda during the last decade, it attracts far more interest since the start of the economic crisis. Moreover, it is likely to be high on the regional development policy agenda for the years to come. The timely and consistent delivery of SGI is critical to the functioning of the modern welfare state which provides implicit and explicit support for the innovative and economically productive parts of the economy. Empirical evidence demonstrates the emergence of such trends in some regions of Europe (ESPON 2013). Historically, rural areas have been disadvantaged when it comes to what is today named as SGI. This has changed during the last decades and three arguments are usually given for this: (1) One of the EU?s key political goals is territorial cohesion, which aims at improving the conditions for the least advantaged regions; (2) SGI forms a central element in the ?European Model of Society?, i.e. access to services is considered a central element of quality of life, and increasing service accessibility a mechanism for overcoming social exclusion and isolation; and (3) SGI addresses the crucial question of what role public authorities should play in societies that are committed to both free markets and social goals (Nugera-Tur et al. 2009). This conclusion can thus be criticised as it only cover the period up to the financial crisis and mainly focuses on infrastructure, i.e. Services of General Economic Interest. SGI is not a homogeneous concept, but contains Services of General Economic Interest and Social Services of General Interest (Foss et al. 2013), and there are significant differences in the provision of Social Services of General Interest (SSGI) at a regional level in the EU (Humer & Palma 2013, Humer 2014). The knowledge gap when it comes to SSGI in rural areas calls for investigation. This paper aims at discussing the provision of SSGI in rural areas and three questions will be addressed: (1) what determines the provision of SSGI in rural areas. (2) How is SSGI provided in rural areas? If we find a gap between how SSGI can be provided and how it is actually provided we face a challenge to overcome which raises the question (3) how can this challenge be addressed?
Keywords: R11; I31; J11; 330; social services of general interest; welfare provision; rural areas